Experimental investigation of the dynamic sealing of shield tail grease under high water pressure. (March 2022) - Shen, Xiang; Yuan, Dajun; Cao, Liqiang; Fu, Yanbin; Jin, Dalong; Gao, Zhenfeng
Graphical abstract: Highlights: Dynamic sealing test device for shield tail grease under high water pressure was developed. Seal failure modes of greases under high water pressure were determined. The progressive failure process of shield tail grease was constructed by ANSYS- Computational Fluid Dynamics (CFD). Abstract: Shield tunnels are often exposed to high water pressures, owing to which, the dynamic sealing of shield tail grease under high water pressure has been rarely studied in the past. In this research, a dynamic sealing test device for the shield tail grease under a high water pressure was developed. Through this test equipment, three representative greases were subjected to sealing tests under different conditions. The influence of high water pressures on the watertightness of greases were investigated. The results demonstrated that the high water pressure considerably influenced the sealing performance of the grease, and the presence of dynamic boundaries facilitated the sealing failure. The wire density of the shield tail brush can be increased to enhance the sealing performance of the shield tail. Besides, Different types of grease have different sealing failure modes. Finally, the results of the model test were verified and analyzed through an ANSYS- Computational Fluid Dynamics (CFD) numerical simulation after calibrating the permeability coefficient. Evaluating the watertightness of the shield tail grease is a prerequisite to ensure the safe construction of a shield tunnel under a high water pressure.